Coherent neutrino scattering off the 48Ti nucleus - Papoulias, D. K.; Kosmas, T. S. (HNPS Advances in Nuclear Physics, 2012)
The method of fractional occupation probabilities of the orbits is adopted in order to obtain nuclear form factors to be used for reliable cross sections calculations of the dominant coherent neutrino-nucleus reaction channel. To this purpose, the multipole decomposition method of Donnelly-Walecka is employed. The response of the 48Ti nucleus in solar and Supernova neutrino detection is investigated through our realistic nuclear structure cross sections calculations, based on the solution of the BCS equations. The present results indicate that the momentum dependence of the nuclear form factors cannot be neglected from the cross section, especially in the energy region of Supernova neutrinos (or for neutrinos having higher energies), because differences of even orders of magnitude may occur.